Phytochemical screening and galactagogue of banana flower (Musa x paradisiaca ABBB) extract on lactating rats - Mahmood, Azizah; Omar, Muhammad Nor; Ngah, Nurziana (2010)
Some plants are known to have high level of phytochemical constituents that promote lactation (galactagogue)for nursing mothers (Goyal, etal, 2008). Herbal galactagogue are recommended by practitioners of the traditional systems of medicine for increasing milk secretion in constituents in banana flower of pisang abu siam (Musa x paradisiaca- ABBB) extract on the effect of galactagogue in lactating rats. Taking into consideration the fact that bana flower is a common plant and considered completely safe and used for centuries both in nutrition and herbal tradition worldwide, the compounds would not have significant side effects and presents no health hazards for users. Lactating rats in treatment groups were fed eith plant extract while mohters in control group were given an equivalent amount of distilled water start from day 5 through fay 14. Sample was administered via oral animal feeding tubes. Milk production was estimated from Day 5 through Day 15 of lactation by isolating the litters (size six) from the dam for 6 hr daily, then weighing the litter before and after 60 minutes of sucklinh. the study showed that rats that were administered with banana flower from the aqueous extract had significantly higher in miik yield compared to control and ethanol extract groups but not signficantly difference in the yeild compared to petroleum ether extract group.